(untitled) (Medical Forum Monthly, 2024)
BACKGROUND: There is no treatment available once get infected with hepatitis B virus. Transfusion of blood contaminated with HBV is one of the major risk factors for increasing its Seroprevalence. Objective: To determine the prevalence of Hepatitis B virus in healthy blood donors . Study Design: A prospective descriptive study Place and duration of study: This study was conducted in department of pathology Combined Military Hospital Multan during a period of three years from 01.07.2007 to 30.06.2010. Patients and Methods: A total number of 18042 blood donors in between 18-55 years of age were screened for transfusion related carriers of infectious diseases including hepatitis B virus by ELIZA technique. Results: Hepatitis B virus suface antigen was detected in 561 (3.1%) Conclusion: Seroprevalence of hepatitis B is high even in healthy and young blood donors. Therefore every donor should be screened for it.